Resilient electrified freight transport: Disruptions and mitigation strategies - Maria Björklund; Henrik Gillström; Fredrik Stahre (Cleaner Logistics and Supply Chain)
The adoption of Heavy Battery Electric Vehicles (H-BEVs) is increasing, and logistics service providers (LSPs) are beginning to transition their fleets. This transition puts new types of challenges on the freight systems, while also likely making them more vulnerable to disruptions. This study fills a gap in the literature by examining the challenges LSPs encounter and the mitigation strategies they use to overcome them during their transition to electrified fleets. The purpose of this study is to explore disruptions and mitigation strategies in electrified freight systems. An interview study was performed with actors in one Nordic country represented by six LSPs operating electric trucks, together with a focus group of 12 participants from 11 organizations representing LSPs, energy companies, platform providers, a transport buyer, a truck manufacturer, and a municipality. Several disruptions that LSPs must handle, many directly or indirectly related to charging, including technical and financial issues. The identified mitigation strategies include, for example, developing information support systems and having extra resources in place. This study provides insights into the research on electrification of freight transport by identifying and describing characteristics of disruptions and mitigation strategies and lays a foundation for understanding aspects that must be considered when implementing and upscaling the use of H-BEVs. Taking an actor perspective, this paper adopts and combines disruption and mitigation frameworks, both of which are lacking in current electrification literature. The results can function as guidelines for actors pursuing H-BEVs regarding what risks need to be handled, and suggestions on how they can be handled, thus constituting an important step in obtaining zero-emission freight systems.